Effect of the dietary supplementation based on essential oils on the quality of gilthead seabream. (28th February 2022) - Iniesta, Celia; Zapata, Elvira; Firmino, Joana P.; Peñaranda, Irene; Egea, Macarena; Linares, Maria Belén; Garrido, Maria Dolores
Abstract: The effectiveness of using essential oils against fish parasites and pathogenic bacteria as environmentally friendly phytotherapeutic agents in the aquaculture industry is demonstrated. A commercial additive composed of garlic essential oil, thymol and carvacrol (AROTEC‐G ® ) was added to a diet for gilthead seabream ( Sparus aurata ) as a protection strategy against Sparicotyle chrysophrii . The intense aromatic properties of these essential oils might lead to the need of a suppression time to reverse possible changes in the organoleptic quality of the fish. Two experimental groups were set up: an experimental group fed a commercial feed supplemented with AROTEC‐G ® (diet A) during the first 4 weeks of the nutritional assay, and after which the treatment was suspended for 14, 21 and 28 days after a first sampling performed (day 0); and a control group, fed the same basal diet without AROTEC‐G ® supplementation (diet C). A physicochemical evaluation measured the pH, colour and texture, and a descriptive quantitative sensory analysis (QDA) was carried out using a trained panel for gilthead seabream fillets. Overall, the findings showed that the use of dietary essential oils did not result in significant sensory differences after day 0 of the study, although slight differences were observed in some of the physicochemical parameters analysed.